Investigação da infecção pelo vírus da hepatite C em indivíduos em situação de rua albergados em Goiânia, Goiás: prevalência e fatores associados - Souza, Jéssyca Pereira e (2017)
Homeless people are at high risk for parental and sexual infections, such as hepatitis C virus (HCV) infection. This study aimed to investigate the epidemiological profile of the infection caused by the hepatitis C virus in homeless people housed in Goiânia, Goiás. This is an observational, cross-sectional and analytical investigation. Between August 2014 and July 2015, 353 homeless people hosted in the only public institution of the state of Goiás were interviewed about sociodemographic characteristics, knowledge and risk factors for hepatitis C, and subsequently tested for the detection of the marker HCV by immunochromatographic test (rapid test) and ELISA. In addition, monitoring of individuals reagentes for HCV was conducted through the information systems of the Unified Health System. The Poisson regression analysis was used to verify the risk factors associated with exposure to HCV with robust variance for the calculation of prevalence ratio (PR). The investigated were mostly male (81.3%), aged between 18 and 45 years (73.62%), singles (59.8%), with no income (35.7), with 5 to 9 years of study (53.3%) and self-reported brown color (61.1%). The study evidenced a knowledge deficit of the homeless people investigated in relation to the HCV transmission. The rapid test used in this study had a high index of agreement with the ELISA, whose sensitivity and specificity was 91.7% and 99.7%, respectively. The overall prevalence of HCV in the homeless people housed was 3.4% (95% CI: 1.9-5.8). It was noted that age (RP: 1.05, 95% CI: 1.02-1.09), be natural from the Southeast region (RP: 2.27, 95% CI: 1.03-5.02), overnight experience in the street (RP: 2.78, 95% CI: 1.11-6.91) and the use of injectable drugs (UID) (PR: 16.59, 95% CI: 4.23-65.09) were statistically associated with HCV infection. Of the 12 housed positive for HCV, only two sought treatment, but there was no adhesion, and another two others evolved to death as a consequence of hepatic cirrhosis due to hepatitis C. The results of the study ratify the extreme condition of homeless people and the increased risk of acquiring and disseminating the hepatitis C virus. Therefore, to prevent and / or minimize risk behaviors for HCV, it is necessary behavioral and structural interventions with combined strategies, such as health education and counseling, permanent education, provision of rapid testing and barrier methods (condom), multidisciplinary treatment, strengthening the strategy of damage reduction, evaluation of policies for homeless people, solidifying the social care equipment provided to this group, such as shelters and access to the services that comprise the health care network.